PROMPTING FACTORS CULTIVATING INDONESIAN EFL LEARNERS’ LEARNING AUTONOMY BEHAVIORS - kristian florensio wijaya (Jurnal Bahasa Lingua Scientia, 2022)
Previous research results unearthed that highly-autonomous EFL learners are more inclined to possess a higher sense of ownership of their learning enterprises owing to the advanced level of learning management. This library study was a further attempt enacted by the researcher to profoundly investigate particular factors believed to cultivate Indonesian EFL learners’ learning autonomy behaviors. In light of this major research objectivity, 30 previous learning autonomy literature were selectively selected to shed clearer enlightenment for Indonesian EFL experts, practitioners, curriculum designers, and educators to start internalizing various meaningful learning activities consolidating learners’ autonomous learning behaviors. Generally speaking, the obtained research results unveiled that the constant nourishment of Indonesian EFL learners’ learning autonomy behaviors can be insured in case second language teachers are committed to promoting more facilitative and innovative learning enterprises in their daily routines. In conformance with these research results, it is of foremost importance for second language teachers to organize their classroom learning dynamics harmonious with learners’ specific learning situations to advance their autonomous learning behaviors to greater development.